Prevalence of Angular Cheilitis and Assessment of Factors Associated with It - A Retrospective Study - Sanjana Devi1 , Revathi Duraisamy2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Angular cheilitis is inflammation of the skin, occurring at the labial commissure – the angle of the mouth.It is an eroded and erythematous non-vesicular lesion that can occur at one or both corners of the mouth.The point of interface for squamous epithelium of the face and oral mucosa is at the angle of the mouth . Itis also a mechanically dynamic hinge for the oral aperture that endures more motion and tensile forces thanthe rest of the lips. Thus, the commissures are especially susceptible to certain stresses. Other names forangular cheilitis include angular cheilosis, angular stomatitis, commissural stomatitis, rhagades, or perleche.The increased prevalence is associated with human immunodeficiency virus, usage of immunosuppressantsand corticosteroids, increased usage of oral prosthesis in the elderly, xerostomia, expanded usage of oralantibiotics, obesity and diabetes to name a few. In young children, angular cheilitis is associated withhabitual lip licking, thumb sucking, or biting of the corners of the mouth, whereas in older patients it occursfrom sagging at the commissures of the mouth. The aim of this study was to assess the prevalence ofangular cheilitis and assessment of factors associated with it. A retrospective study was conducted in theSaveetha Dental College, Chennai, India. Ethical clearance was obtained from SRB committee, SaveethaDental College, Chennai, India. The clinical portion of this retrospective study was conducted over a 9month period,i.e, between June, 2019 to March,2020. Some patients reported with pain while for others itwas observed during routine examination. Data was collected from a total of 86000 patients who visitedSaveetha dental college between Jun,2019 to March,2020. Out of this, the data of 57 patients who visitedthe institute and were diagnosed with angular cheilitis were retrieved. The data obtained was tabulated inSPSS for windows, version 20. Descriptive statistics were analysed. Chi square test was done to analyseassociation of habits of the patient with age, gender,dental status and systemic diseases of patients withangular cheilitis. The results of the study indicated angular cheilitis was more predominant in males and itwas more predominant between 40-49 years of age. Angular cheilitis was more predominant in completelyedentulous patients and diabetes was the most common systemic disease among the patients. There wasstatistically significant association between gender (P=0.002) and habits of the patient. However, there wasno statistically significant association between age(P=0.278), dental status (P=0.137) and systemic diseases(P=0.817) with habits of the patient.